Management of Federally Sponsored Libraries: Case Studies and Analysis, 1st edition - Missar, Charles D. (Routledge, 2020)
In this book, first published in 1995, managers from seven federally sponsored libraries in the United States analyse in detail their roles and responsibilities. Each librarian writes about the management of their facility and highlights significant features about its collection and services. It brings together in one place detailed descriptions of the scope and strengths of federal libraries, the kinds of services they provide, and the manner in which they function. The book provides readers with a unique opportunity to learn about such libraries from the manager's point of view and shows how these facilities are organized, how they use their resources, what equipment and services exist for interlibrary loans and for reference services, and what databases they use to serve patrons.